Impact of donor CYP3A5 genotype on pharmacokinetics of tacrolimus in South African paediatric liver transplant patients - Wheeler, Caitlin (My University, 2024)
Tacrolimus is characterised by a narrow therapeutic target range and wide interpatient variability. Pharmacogenetic research attributes CYP3A5 single nucleotide polymorphisms to the variable inter-patient tacrolimus concentration dose ratios (CDR). In this study, we compared the mean tacrolimus CDR in paediatric liver transplant recipients and their living liver donors’ CYP3A5 rs776746 T>C genotypes(*1/*1, *1/*3 and *3/*3), accounting for donor and recipient characteristics. The graft-to-recipient weight ratio and the CYP3A5 donor genotypes were found to be independent factors significantly impacting the mean tacrolimus CDR. Donor CYP3A5 expressors (*1/*1 and *1/*3) were shown to have significantly lower recipient tacrolimus CDRs, therefore, higher dosages would be required in comparison to CYP3A5 non-expressors to reach the same therapeutic target range. The potential implementation of a stratified medicine dosage algorithm, combining living liver donor CYP3A5 genotyping with the calculation of the graft-to-recipient weight ratio, may predict the optimal tacrolimus dosage schedules for liver transplant recipients.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Science in Medicine to the Faculty of Health Sciences, University of the Witwatersrand, School of Pathology, Johannesburg, 2023
Keywords: Tacrolimus; Pharmacogenetic; Nucleotide polymorphisms; SDG-3: Good health and well-being